Improving the reading comprehension and motivation level of struggling adolescent readers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Palmerston North, New Zealand - Jeriffe, Desma (Massey University, 2013)
Adolescents from many parts of the world are struggling to read and comprehend text at their appropriate grade level. As a result of their repeated failure in reading comprehension tasks, many of these struggling adolescent readers lose their motivation to read and consequently become disengaged with reading. The aim of this research project was to determine the effectiveness of a reading intervention programme at improving the reading comprehension and motivation level of struggling adolescent readers. The intervention was designed based on the Concept Oriented Reading Instruction (CORI) Programme developed by John Guthrie and colleagues. The four week intervention which included a total of 15 forty minute lessons was carried out with seven struggling adolescent readers from the Caribbean island of Saint Lucia. The research project utilized a mixed-method approach in which both quantitative and qualitative data was collected. The Neale Analysis of reading ability was used to assess the reading comprehension level of the students while a motivation questionnaire was used to assess the motivation level of the students. A pre-test and post-test method was used in administering these instruments. Field notes were also taken based on general observations of the participants exposed to the intervention. The results from the data indicated that there was a general improvement in students‘ reading comprehension and motivation level at the end of the intervention.
Keywords: Reading comprehension; Teenagers and reading; Reading comprehension, Saint Lucia; Adolescent readers; Reading motivation; Reading ability; Reading intervention programme